France's Autism Controversy and the Historical Role of Psychoanalysis in the Diagnosis and Treatment of Autistic Children. Issue 2 (July 2020) - Bates, Richard
Abstract : Autism is a contested and controversial subject in many countries, but France has experienced more controversy around the issue than most. This article draws attention to the circumstances in which the formerly prominent role of psychoanalysis in the diagnosis and treatment of autism in children in France has led to much animated debate and eventually to changes in public policy, following internal and international pressure. After outlining these recent events, it will consider the reasons why France found itself out of line with other countries for many years, by examining the historical role of certain influential individuals in the psychoanalytical circle close to Jacques Lacan (1901–81), in particular the child specialists Françoise Dolto (1908–88) and Maud Mannoni (1923–98).